The Nuremberg code and ethical principles of a psychologist’s aсtivity - A. Yu. Odynets (Ukrainian Cultural Studies, 2022)
It is hard to imagine the horrors that took place during the Second World War. Concentration camps began to appear almost immediately after Adolf Hitler came to power in Germany. The goal of such camps is the isolation, slave exploitation and destruction of all whom the Nazis considered enemies of both the German people and the state itself. The worst thing is that the people who were taken to such camps had no idea what was waiting for them there. The term of their stay was indefinite, they left their homes, not knowing that they would never return to them. All that fear, pain, despair, misunderstanding is hard to comprehend and describe in words.